Regional event-based surveillance in WHO’s Western Pacific Region (Western Pacific Surveillance and Response, 2020)
In the World Health Organization’s Western Pacific Region, event-based surveillance has been conducted for more than a decade to rapidly detect and assess public health events. This report describes the establishment and evolution of the Western Pacific Region’s event-based surveillance system and presents an analysis of public health events in the Region. Between July 2008 and June 2017, a total of 2396 events were reported in the Western Pacific Region, an average of 266 events per year. Infectious diseases in humans and animals accounted for the largest proportion of events recorded during this period (73%, 1743 events). Maintaining and strengthening this well established system is critical to support the rapid detection, assessment and response to public health events to sustain regional health security.